2009
DOI: 10.1007/s00423-009-0547-z
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of risk factors for pancreatic fistula after pancreaticoduodenectomy: clinical impact of bile juice infection on day 1

Abstract: Bile juice infection on day 1 was a significant risk factor for grade B or grade C POPF after pancreaticoduodenectomy. Although the performance or the status of biliary drainage itself was not a risk factor for POPF, percutaneous biliary drainage might be advantageous against retrograde drainage to reduce the risk of biliary infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 24 publications
1
38
1
1
Order By: Relevance
“…This finding is supported by those of other reports, 31,39 but the underling pathogenesis remains unclear. In our institute, POPF was more frequent in men than in women, 38 which could be attributed to the increased incidence of DGE in men.…”
Section: Discussionmentioning
confidence: 70%
“…This finding is supported by those of other reports, 31,39 but the underling pathogenesis remains unclear. In our institute, POPF was more frequent in men than in women, 38 which could be attributed to the increased incidence of DGE in men.…”
Section: Discussionmentioning
confidence: 70%
“…Jagannath and co‐workers reported that a positive intraoperative bile culture was associated with infectious complications. In this context, it has been reported that PTBD may reduce the risk of biliary infection. However, PTBD catheter‐tract cancer recurrence was detected in 5·2 per cent of patients with cholangiocarcinoma undergoing resection, suggesting that PTBD should be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…These risk factors can be classified into three categories: patient-related factors, pancreatic anatomy, and surgical techniques. Patient-related factors include age, gender, body mass index, visceral fat area, preoperative biliary drainage, and associated co-morbidities [1][2][3][4][5][6][7][8]. Factors related to pancreatic anatomy include soft pancreatic texture, small diameter of the pancreatic duct, fatty pancreas, and postoperative pancreatitis [3,[8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%